Rabies Immunization of Travelers in a Canine Rabies Endemic Area. Issue 3 (8th March 2013) - Sibunruang, Suda; Tepsumethanon, Saowaluck; Raksakhet, Natthasri; Tantawichien, Terapong
Abstract: Background: Travelers to countries where rabies is endemic may be at risk of rabies exposure. We assessed rabies immunization of travelers attending a travel clinic in Thailand. Methods: The medical charts of international travelers who came for preexposure (PrEP) or postexposure (PEP) rabies prophylaxis at the Queen Saovabha Memorial Institute (QSMI), Bangkok, Thailand between 2001 and 2011 were retrospectively reviewed. Results: A total of 782 travelers, including 188 patients who presented with mammal‐associated injuries and possible rabies exposures and 594 persons who came requesting PrEP, were studied. Of the travelers who received PEP, only 27 (14.3%) had been previously immunized against rabies and 141 (75.0%) cases experienced high‐risk WHO category III exposure. Most of the incidents were unprovoked. Although promptly seeking medical services after the injuries, 114 (60.7%) travelers did not undertake any first‐aid care for their wounds. Of these travelers, 19 (10.3%) received intradermal rabies vaccination as they could complete the series here. Rabies immunoglobulin was given to 118 of 121 (97.5%) patients. About one fourth of recipients could accomplish the full schedule at QSMI. Among visitors who requested PrEP, 454 (76.4%) persons had just started their first dose. Among all visitors, 263 (44.3%) were Japanese. The number of Japanese asking for PrEP was higher in 2006, the year when cases of imported human rabies to Japan were reported. This trend has sustained since then. Two (0.3%) travelers were bitten by suspected rabid dogs before they completed their PrEP program. Conclusion: Rabies prophylaxis is an important decision for each traveler. It should be made before visiting endemic areas.